The origin(s) of Natya: Natya versus ritual - Gonc-Moačanin, Klara (2003)
Many theories about the origin of natya (Mueller, Hillebrandt, Kuiper, Lidova, Levi, Renou) present only partial pictures of it. Classical Indian theatre can have a partially ritual origin, but is no ritual. Ritual has religious goals, and theatre has aesthetic goals. The Natyasastra, the classical handbook of Indian drama, gives, esp. in chapters 1 and 4, stories of the origin of drama and of the first performances that can reveal us more about that origin than it was so far supposed. They confirm the view that the natya - even for the gods in those stories - was no ritual, but a means for amusement both to be seen and to be heard. The stories can be mythological, but they are enacted by dialogues, singing, dancing and combining many aspects of performance to enhance the aesthetical experience of the drama. An interdisciplinary research might in future give a fuller picture of natya's origins.
Projekt MZOS
ENG